1990
DOI: 10.2169/internalmedicine1962.29.560
|View full text |Cite
|
Sign up to set email alerts
|

Acute autonomic neuropathy associated with a high serum bradykinin level and positive anti-nuclear and anti-DNA antibodies titers.

Abstract: A hypotensive 37-year-old man developed the problems of impotence, lack of sweating, orthostatic hypotension, and convulsive syncopal attack. His blood pressure fell to 53 mmHgsystolic following bedtilting from 30 to 60°, but his heart rate remained constant which indicated a diagnosis of acute autonomic neuropathy. With the tilting test, a decrease in serum cathecholamine levels and an increase in bradykinin levels were observed. Four months after admission, anti-nuclear antibody, anti-DNAantibody, and the LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…[11][12][13][14][15] An autoimmune mechanism has been suggested as a causal mechanism in both POTS and CFS, 2,3,7,14,16 due to frequent findings of autoantibodies (including ANA) in POTS/CFS patients. [17][18][19][20][21][22] More specifically, ganglionic A3 acetylcholine receptor antibodies are found in at least one in seven POTS patients. 7 Moreover, various autoantibodies, including those directed against cardiac proteins, 21 b1/2-adrenergic, M2/3 muscarinic 23 and N-type acetylcholine receptors, 7 have been identified in POTS patients, strengthening the idea of POTS as member of the autoimmune autonomic neuropathies family.…”
mentioning
confidence: 99%
“…[11][12][13][14][15] An autoimmune mechanism has been suggested as a causal mechanism in both POTS and CFS, 2,3,7,14,16 due to frequent findings of autoantibodies (including ANA) in POTS/CFS patients. [17][18][19][20][21][22] More specifically, ganglionic A3 acetylcholine receptor antibodies are found in at least one in seven POTS patients. 7 Moreover, various autoantibodies, including those directed against cardiac proteins, 21 b1/2-adrenergic, M2/3 muscarinic 23 and N-type acetylcholine receptors, 7 have been identified in POTS patients, strengthening the idea of POTS as member of the autoimmune autonomic neuropathies family.…”
mentioning
confidence: 99%
“…BK was further investigated and reported to reduce blood pressure and cause the slow contraction of the gut and was hence named BK (brady = slow, and kinin = move) (15). Previously, increased levels of BK were reported in patients with acute autonomic neuropathy (16), and the authors suggested its association with SLE. Several studies reported the role of angiotensin-converting enzyme (ACE) gene polymorphisms in SLE, but thus far, no study has directly measured the levels of BK and BK-des-arg-9 in SLE or RA (17).…”
Section: Discussionmentioning
confidence: 99%